Pop Culture and English Language Learning Motivation among Ab-English Students - Placer, Marie Franchesca; Ngo, Cristy Grace; Nano, Sonairah; Calambro, Aimae (International Journal Corner of Educational Research, 2024)
The study on Pop Culture and English Language Motivation was a descriptive correlational study conducted among the ninety-five (95) AB-English students at the University of Mindanao-Matina Campus, Davao City. This study aims to discover the prevalent relationship between the use of pop culture and English language learning motivation. Adopted questionnaires were utilized as a research instrument to gather the data, which were analyzed using mean, standard deviation, and Pearson's r correlation. The study also used total population sampling to select the number of respondents. Based on the findings, there is a high level of pop culture use, particularly on other media platforms, such as English cinema, music, and mobile phones. Moreover, AB-English students have a very high integrative and instrumental motivation to learn the language. Finally, the overall correlation for both variables suggest a moderate positive correlation with a threshold of 0.567, implying that learners with a high-level use of pop culture media are more likely to be integratively and instrumentally motivated to learn English, especially when using other media platforms, such as English cinema, music, and mobile phones.